The relationship between product quality and brand loyalty: a case study of Motosikal dan Enjin Nasional Sdn. Bhd. (Modenas) / Mohd Rizaimy Shaharudin, Azfahanee Zakaria and Anita Abu Hassan - Shaharudin, Mohd Rizaimy; Zakaria, Azfahanee; Abu Hassan, Anita (Research Management Institute (RMI), 2009)
This study is about the discoveries on the relationship between intrinsic and extrinsic attributes of product quality with brand loyalty. It helps to extend the understanding on the perceptions of product quality of Malaysia national brand motorcycle/scooter, MODENAS and its influence towards brand loyalty, an important element in determining the customer repurchase buying behavior. To date, there have been a very minimum studies were conducted by taking into consideration of the product quality and brand loyalty in motorcycle industry in Malaysia. Though, there are some studies done in this field but most of them are based in United States and United Kingdom. Therefore from the data presented in this study, it can be expected that the findings can benefit both industrial and academician by giving a new source of ideas and information. Results indicated that although from the earlier literature concluded product quality generally has significant influences towards the brand loyalty but in the case of motorcycle/scooter product, only product quality based on the perceived quality (extrinsic attribute) was found significantly influence on the brand loyalty instead of objective quality (intrinsic attributes). It would seem reasonable to suppose that perceptions of a good product quality from extrinsic attributes will develop a brand loyalty due to the feelings and affects formed as a result of the perception of quality. These perceptions are not fixed and can be changed if the product has high level of customer awareness, good image from marketing activities such as advertising, sales promotion and etc. Future research should focus on the similar study of product quality and brand loyalty to the other brand being the competitor to MODENAS in the market. By doing this only the gap can be closed with a clearer picture on the extended scope of market environment can be examined. Eventually, a comparison can be made between the findings of the three brands so that such constructible findings and conclusions can be made to the study.